Mutual exacerbation of peroxisome proliferator‐activated receptor γ coactivator 1α deregulation and α‐synuclein oligomerization. Issue 1 (19th December 2014) - Eschbach, Judith; von Einem, Björn; Müller, Kathrin; Bayer, Hanna; Scheffold, Annika; Morrison, Bradley E.; Rudolph, K. Lenhard; Thal, Dietmar R.; Witting, Anke; Weydt, Patrick; Otto, Markus; Fauler, Michael; et al.
<x xml:space="preserve">Abstract</x> Objective Aggregation of α‐synuclein (α‐syn) and α‐syn cytotoxicity are hallmarks of sporadic and familial Parkinson disease (PD), with accumulating evidence that prefibrillar oligomers and protofibrils are the pathogenic species in PD and related synucleinopathies. Peroxisome proliferator‐activated receptor γ coactivator 1α (PGC‐1α), a key regulator of mitochondrial biogenesis and cellular energy metabolism, has recently been associated with the pathophysiology of PD. Despite extensive effort on studying the function of PGC‐1α in mitochondria, no studies have addressed whether PGC‐1α directly influences oligomerization of α‐syn or whether α‐syn oligomers impact PGC‐1α expression. Materials and Methods We tested whether pharmacological or genetic activation of PGC‐1α or PGC‐11α knockdown could modulate the oligomerization of α‐syn in vitro by using an α‐syn ‐fragment complementation assay. Results In this study, we found that both PGC‐1α reference gene (RG‐PGC‐1α) and the central nervous system (CNS)‐specific PGC‐1α (CNS‐PGC‐1α) are downregulated in human PD brain, in A30P α‐syn transgenic animals, and in a cell culture model for α‐syn oligomerization. Importantly, downregulation of both RG‐PGC‐1α and CNS‐PGC‐1α in cell culture or neurons from RG‐PGC‐1α–deficient mice leads to a strong induction of α‐syn oligomerization and toxicity. In contrast, pharmacological activation or genetic overexpression of RG‐PGC‐1α reduced α‐syn oligomerization and rescued α‐syn–mediated toxicity. Interpretation Based on our results, we propose that PGC‐1α downregulation and α‐syn oligomerization form a vicious circle, thereby influencing and/or potentiating each other. Our data indicate that restoration of PGC‐1α is a promising approach for development of effective drugs for the treatment of PD and related synucleinopathies. ANN NEUROL 2015;77:15–32